Microprobe techniques in SAW measurements - CHILLA, E.; HESJEDAL, T.; FRÖLICH, H.-J, (Archives of Acoustics, 1996)
Starting from the conventional microprobe techniques, a scanning acoustic tunneling microscope (SATM) and a scanning acoustic force microscope (SAFM) have been developed to detect particle displacements at solid surfaces up to GHz frequencies. Based on the non-linear dependence of the tunneling current in SATM and of the forces in SAFM on the tip to surface distance, respectively, it is demonstrated that wave field parameters of surface acoustic waves can be measured with a lateral resolution in the submicrometer range.